Nano-diamond / graphene composite vertical sheet thin film electrode and preparation method thereof
The surface components of nanodiamond/graphene composite vertical film electrode are regulated through microwave plasma etching, which solves the problems of narrow electrochemical windows and complex deposition processes, and realizes high capacitance electrode materials, significantly improving electricity Chemical properties.
Patent Information
- Application Number
- CN202310203918.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-06
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2043-03-06
AI Technical Summary
The existing diamond/graphene composite 3D electrodes have a narrow electrochemical window during the electrochemical process, resulting in charge transfer to the solution, reducing the capacitance performance of the electrode, and the chemical vapor deposition growth process is complicated, so it is impossible to finely regulate graphene and diamond on the electrode surface. Components.
Using microwave argon/oxygen mixed plasma etching treatment, the surface components of nanodiamond/graphene composite vertical sheet film electrode are regulated, and the graphite phase is preferentially etched through plasma, and the graphite layer is peeled off to form a single layer/small layer of graphite. An ene-coated diamond-coated vertical sheet structure grows on a single-particle nanodiamond film.
The electrode's double layer capacitance value has been significantly improved to reach 1626.47μF/cm2, far exceeding the conventional three-dimensional B-doped diamond electrode. The process is simple and easy to operate, and has a wide range of application prospects.
Smart Images

Figure HDA0004110062220000011 
Figure HDA0004110062220000012 
Figure HDA0004110062220000021
Abstract
Description
Technical Field
[0001] The invention relates to a nano-diamond / graphene composite vertical sheet film electrode with supercapacitor characteristics and a preparation method thereof. Background Art
[0002] Diamond has been used to construct high-performance electrochemical energy storage devices due to its wide electrochemical potential window (~3.3V) in aqueous solution and long service life. The double-layer capacitance of B-doped diamond thin film electrodes is about 4 to 6 μF / cm 2 In order to increase the capacitance, the researchers constructed a 3D electrode with a high specific surface area, which increased the capacitance to 11-15 μF / cm 2 However, the double-layer capacitance is still low and fails to meet the requirements of practical applications.
[0003] Graphene can gather high loads of charge, and people use diamond / graphene composites to form 3D electrodes to improve capacitance performance. Current reports show that thick graphite (more than 10 layers) wrapped in diamond to form a 3D composite electrode has a double-layer capacitance of 147μF / cm 2 In the early stage, we embedded nanodiamonds into vertical graphite sheets to form a 3D composite electrode, and the double-layer capacitance value was increased to 627μF / cm 2 , and obtained higher capacitance performance than B-doped diamond 3D electrode. However, the graphene content in the above diamond / graphene composite 3D electrode is high, and the electrochemical window is narrowed (~2.8V). Therefore, the hydrogen evolution and oxygen evolution reaction occurring in the electrode during the electrochemical process causes the charge to be transferred to the solution, that is, it is difficult for the electrode to load the charge to form a capacitor, which reduces the capacitance performance of the electrode. This shows that regulating the relative content of graphene and diamond on the surface of the diamond / graphene composite 3D electrode and appropriately increasing the diamond content to expand the electrochemical window of the electrode is expected to improve the capacitance performance of the film. However, the chemical vapor deposition growth process and growth atmosphere of the above composite 3D electrode are complex, and it is impossible to finely control the graphene and diamond components on the electrode surface. Therefore, developing a post-treatment method to regulate the surface components of the film is extremely important for obtaining a diamond / graphene composite 3D electrode with high capacitance characteristics. Summary of the invention
[0004] The present invention utilizes the characteristic of plasma preferentially etching the graphite phase to precisely control the graphite and diamond components on the electrode surface, peels off the graphite layer by layer on the diamond / vertical graphite composite sheet, and obtains a vertical sheet structure of single-layer / few-layer graphene-coated diamond. This vertical sheet structure is grown on the single-granular layer nanodiamond film in our authorized patent ZL201510149374.4, and the constructed 3D electrode has a large double-layer capacitance.
[0005] To achieve the above object, the present invention adopts the following technical solution:
[0006] A nano-diamond / graphene composite vertical sheet thin film electrode, wherein the nano-diamond / graphene composite vertical sheet thin film electrode is prepared according to the following method:
[0007] (1) Pretreatment of single crystal silicon substrate surface grinding and seeding: diamond powder and glycerol are fully dispersed and mixed to obtain diamond grinding paste; the diamond grinding paste is taken on a polishing flannel cloth, and the intrinsic single crystal silicon wafer is (gently) pressed back and forth on the grinding paste for 5 to 40 minutes (preferably 30 minutes); the polished silicon wafer is ultrasonically cleaned in acetone and anhydrous ethanol for 1 to 30 minutes (preferably 5 minutes) in turn, and dried with nitrogen to obtain single crystal silicon after seeding;
[0008] (2) Hot Wire Chemical Vapor Deposition Thin Film Growth: The seeded single crystal silicon described in step (1) is placed as a substrate in a hot wire chemical vapor deposition device, and acetone is used as a carbon source. The acetone is introduced into the reaction chamber by bubbling hydrogen at a flow rate of 70-110 sccm (preferably 90 sccm). Pure hydrogen at a flow rate of 100-300 sccm (preferably 200 sccm) is also introduced. The growth power is controlled to be 2000-2600 W (preferably 2200 W) and the growth pressure is controlled to be 1.0-2.5 kPa (preferably 1.6 kPa) to grow a nano-diamond particle layer for 10-50 m in (preferably 20 min); adjust the pure hydrogen flow rate to 0-20 sccm (preferably 0 sccm), the hydrogen flow rate (i.e., acetone flow rate) to 50-100 sccm (preferably 100 sccm), reduce the power to 1300-1800 W (preferably 1800 W), and grow the vertical nano-diamond / graphene composite sheet for 0.5-10 min (preferably 3 min); stop passing the pure hydrogen and acetone, and slowly reduce the power to 0 at a rate of 0.1-5 V / min (preferably 0.5 V / min) to obtain a silicon wafer containing vertical nano-diamond / graphene composite sheets;
[0009] (3) Microwave argon / oxygen mixed plasma etching treatment: Place the silicon wafer containing the vertical nano-diamond / graphene composite layer described in step (2) in a microwave plasma vapor deposition device, introduce argon plasma or a mixed plasma of argon and oxygen, control the power to 400-800 W (preferably 600 W), the gas pressure to 10-20 Torr (preferably 15 Torr), the processing time to 2-8 min (preferably 4 min), and the total plasma flow rate to 80-120 sccm (preferably 100 sccm), to obtain the nano-diamond / graphene composite vertical layer thin film electrode; when the mixed plasma of argon and oxygen is introduced, the oxygen flow rate is 0-5 sccm (where 0 is infinitely close to 0 but not 0).
[0010] Among them, the oxygen flow rate is crucial to the capacitance of the nano-diamond / graphene composite vertical sheet film of the present invention, and too high an oxygen flow rate will weaken the capacitance.
[0011] Furthermore, the diamond powder described in step (1) has a particle size of 500 nm and is purchased from Zhecheng Huifeng Diamond Technology Co., Ltd. in one embodiment of the present invention.
[0012] Furthermore, in step (1), the present invention recommends that the diamond powder and glycerol be fully dispersed and mixed by ultrasonic dispersion for 10 to 30 minutes, and in one embodiment of the present invention, for 20 minutes.
[0013] Furthermore, the volume of the glycerol in step (1) is 50-150 mL / g (preferably 90-110 mL / g, particularly preferably 100 mL / g) based on the mass of the diamond powder.
[0014] Further, in one embodiment of the present invention, the intrinsic single crystal silicon wafer in step (1) is a single-sided polished silicon wafer of Zhejiang Lijing Optoelectronics Technology, with a thickness of 500±10μm, a diameter of 100±0.4mm, a resistivity of 0.011-0.01Ωcm, and a model / crystal orientation: P <100> .
[0015] Preferably, only argon plasma is introduced in step (3).
[0016] The present invention particularly recommends that the nano-diamond / graphene composite vertical sheet thin film electrode be prepared according to the following method:
[0017] (1) Pretreatment of single crystal silicon substrate surface grinding and seeding: diamond powder and glycerol are fully dispersed and mixed to obtain diamond grinding paste; the diamond grinding paste is taken on a polishing flannel cloth, and an intrinsic single crystal silicon wafer is pressed back and forth on the grinding paste for 30 minutes. The polished silicon wafer is ultrasonically cleaned in acetone and anhydrous ethanol for 5 minutes in turn, and dried with nitrogen to obtain single crystal silicon after seeding;
[0018] The volume of the glycerol is 100 mL / g based on the mass of the diamond powder;
[0019] (2) Hot wire chemical vapor deposition thin film growth: the single crystal silicon after seeding described in step (1) is placed as a substrate in a hot wire chemical vapor deposition device, acetone is used as a carbon source, and the acetone is introduced into the reaction chamber by bubbling hydrogen with a flow rate of 90 sccm. At the same time, a flow rate of 200 sccm is introduced, and the growth power is controlled to be 2200 W and the growth pressure is 1.6 kPa to grow a nano-diamond particle layer for 20 minutes; the pure hydrogen flow rate is adjusted to 0 sccm and the hydrogen flow rate is 100 sccm, and the power is reduced to 1800 W to grow a vertical nano-diamond / graphene composite layer for 3 minutes; the introduction of pure hydrogen and acetone is stopped, and the power is slowly reduced to 0 at 0.5 V / min to obtain a silicon wafer containing a vertical nano-diamond / graphene composite layer;
[0020] (3) Microwave argon plasma etching treatment: Place the silicon wafer containing the vertical nanodiamond / graphene composite layer described in step (2) in a microwave plasma vapor deposition device, and introduce argon plasma, wherein the argon flow rate is 100 sccm; control the power to 600 W, the gas pressure to 15 Torr, and the processing time to 4 min to obtain the nanodiamond / graphene composite vertical layer thin film electrode.
[0021] Compared with the prior art, the beneficial effects of the present invention are mainly reflected in: 1. The composite film is processed by microwave plasma chemical vapor deposition equipment to adjust the relative content of graphene and diamond on the surface of the film. The preparation is simple and easy to operate, and the capacitance performance of the film is greatly improved without doping; 2. The film electrode has an extremely high capacitance value of 1626.47μF / cm 2 , is a conventional three-dimensional B-doped diamond electrode (11-15 μF / cm 2 ) and has great application prospects in the electrode materials of double-layer supercapacitors. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 FESEM image of NCD-VG0 sample with oxygen content of 0 sccm in plasma;
[0023] Figure 2 is the Raman spectrum of NCD-VG0 sample with oxygen content of 0 sccm in plasma;
[0024] Figure 3 HRTEM image of NCD-VG0 sample with oxygen content of 0 sccm in plasma;
[0025] Figure 4 CVs of NCD-VG0 sample with 0 sccm oxygen content in plasma at a scan rate of 0.1-0.5 V / s in 1 M KOH electrolyte;
[0026] Figure 5 FESEM image of NCD-VG2 sample with oxygen content of 2 sccm in plasma;
[0027] Figure 6 Raman spectrum of NCD-VG2 sample with 2 sccm oxygen content in plasma;
[0028] Figure 7 HRTEM image of NCD-VG2 sample with oxygen content of 2 sccm in plasma;
[0029] Figure 8 CVs of NCD-VG2 sample with 2 sccm oxygen content in plasma at scan rates of 0.1-0.5 V / s in 1 M KOH electrolyte;
[0030] Fig. 9 FESEM image of NCD-VG5 sample with oxygen content of 5 sccm in plasma;
[0031] Fig.10 is the Raman spectrum of NCD-VG5 sample with 5 sccm oxygen content in plasma;
[0032] Fig.11 HRTEM image of NCD-VG5 sample with oxygen content of 5 sccm in plasma;
[0033] Fig.12 CVs of NCD-VG5 sample with 5 sccm oxygen content in plasma at a scan rate of 0.1-0.5 V / s in 1 M KOH electrolyte; DETAILED DESCRIPTION
[0034] The present invention is further described below by means of specific embodiments, but the protection scope of the present invention is not limited thereto.
[0035] Example 1
[0036] Diamond powder (Zhecheng Huifeng Diamond Technology Co., Ltd., particle size 500nm) and glycerol (glycerol) were mixed in a ratio of 1g:100ml, and ultrasonically dispersed for 20min to obtain diamond grinding paste; the diamond grinding paste was taken on a polishing flannel cloth and pressed on an intrinsic single crystal silicon wafer (Zhejiang Lijing Optoelectronics Technology, single-sided polished silicon wafer, thickness 500±10μm, diameter 100±0.4mm, resistivity 0.011-0.01Ωcm, model / crystal orientation: P <100> ) was polished back and forth at the grinding paste for 30 minutes, and the processed silicon wafer was ultrasonically cleaned in acetone and anhydrous ethanol for 5 minutes in turn, and dried with nitrogen to obtain single crystal silicon after seeding; the single crystal silicon after seeding was placed in a hot wire chemical vapor deposition device as a substrate, and acetone was used as a carbon source. The acetone was introduced into the reaction chamber by bubbling hydrogen with a flow rate of 90sccm, and pure hydrogen with a flow rate of 200sccm was also introduced. The growth power was controlled to 2200W and the growth pressure was 1.6kPa to grow a nano diamond particle layer for 20 minutes; the pure hydrogen flow rate was adjusted to 0sccm, the acetone flow rate was 100sccm, and the power was reduced to 1800W, grow vertical nano-diamond / graphene composite sheets for 3 minutes; stop introducing acetone, and slowly reduce the power to 0 at a rate of 0.5V / min to obtain a silicon wafer containing vertical nano-diamond / graphene composite sheets; place the silicon wafer with vertical nano-diamond / graphene composite sheets in a microwave plasma vapor deposition device, and introduce argon and oxygen mixed plasma, wherein the total flow rate of argon and oxygen is 100sccm; control the power to 600W, the gas pressure to 15Torr, the processing time to 4min, and control the oxygen flow rate in the plasma to 0sccm to obtain a nano-diamond / graphene composite vertical sheet film.
[0037] The surface morphology of the film was observed by field emission scanning electron microscopy; the phase composition of the sample was detected by visible light Raman spectroscopy; the microstructure of the sample was analyzed by high-resolution transmission electron microscopy; and the electrochemical properties of the film were determined by an electrochemical workstation.
[0038] Figure 1 This is a field emission scanning electron microscope photo of the NCD-VG0 sample with an oxygen content of 0 sccm at 50,000 times. It can be seen that the lamellar structure between the particles remains intact, and the film thickness is about 1.76μm.
[0039] Figure 2 This is the visible light Raman spectrum of the NCD-VG0 sample with an oxygen content of 0 sccm. The 1350, 1580, 1620 and 2700 cm -1 Four characteristic peaks, 1350cm -1 For sp 2 Disordered or defective D peak associated with bonded carbon, 1580 cm -1 For sp 2G peak of bonded carbon, 1620 cm -1 D' peak related to graphite edge defects, also the characteristic peak of vertical graphene, 2700cm -1 It is a 2D peak with double frequency Raman characteristics due to the complete dispersion of phonons associated with single-layer or few-layer graphene. D / I G The value is 2.03, indicating that there are a lot of defects inside the film. The half-peak width of the G peak is 39.31 cm -1 , indicating that the degree of disorder of graphite inside the film is low.
[0040] Figure 3 HRTEM image of NCD-VG0 sample with oxygen content of 0 sccm. Figure 3 a in the figure is a low-power image of the NCD-VG0 sample, in which a clear vertical lamella structure can be seen outside the particle, with a height of about 500nm. The enlarged image of the typical position of the lamella part is shown in Figure 3 b and Figure 3 c in the figure, and the Fourier transform image on the far right. The SAED image shows discrete diffraction spots on the graphite (002) and diamond (111)(220) planes, indicating the existence of single crystal structures of graphite and diamond. Figure 3 In b, diamond particles with a 0.25 nm interplanar spacing (~5 nm) and a multilayer graphite structure tightly wrapped around them are clearly visible. Figure 3 In the figure c, we can see the obvious multi-layer graphite ribbons. From the edge to the inside, the number of graphite layers gradually increases and the graphite becomes thicker. Therefore, it can be seen that the NCD-VG0 sample is composed of nanodiamond particles wrapped in multi-layer graphite mixed with multi-layer graphite ribbons.
[0041] Figure 4 The CV curves of NCD-VG0 samples with an oxygen content of 0 sccm at different scan rates are shown in Figure 2. It can be seen that the shape is close to a rectangle, indicating that it has certain double-layer capacitance characteristics, and as the scan rate increases, the area of the CV curve also increases, which is caused by the increase in the diffusion resistance of electrolyte ions on the film surface, and is expressed by the formula The calculated surface capacitance at a scanning voltage of 0.1 V / s is 1626.47 μF / cm 2 , showing higher capacitance.
[0042] Example 2
[0043] Diamond powder (Zhecheng Huifeng Diamond Technology Co., Ltd., particle size 500nm) and glycerol (glycerol) were mixed in a ratio of 1g:100ml, and ultrasonically dispersed for 20min to obtain diamond grinding paste; the diamond grinding paste was taken on a polishing flannel cloth and pressed on an intrinsic single crystal silicon wafer (Zhejiang Lijing Optoelectronics Technology, single-sided polished silicon wafer, thickness 500±10μm, diameter 100±0.4mm, resistivity 0.011-0.01Ωcm, model / crystal orientation: P <100> ) was polished back and forth at the grinding paste for 30 minutes, and the processed silicon wafer was ultrasonically cleaned in acetone and anhydrous ethanol for 5 minutes in turn, and dried with nitrogen to obtain single crystal silicon after seeding; the single crystal silicon after seeding was placed in a hot wire chemical vapor deposition device as a substrate, and acetone was used as a carbon source. The acetone was introduced into the reaction chamber by bubbling hydrogen with a flow rate of 90sccm, and pure hydrogen with a flow rate of 200sccm was also introduced. The growth power was controlled to 2200W and the growth pressure was 1.6kPa to grow a nano diamond particle layer for 20 minutes; the pure hydrogen flow rate was adjusted to 0sccm, the acetone flow rate was 100sccm, and the power was reduced to 1800W, grow vertical nano-diamond / graphene composite sheets for 3 minutes; stop introducing acetone, and slowly reduce the power to 0 at a rate of 0.5V / min to obtain a silicon wafer containing vertical nano-diamond / graphene composite sheets; place the silicon wafer with vertical nano-diamond / graphene composite sheets in a microwave plasma vapor deposition device, and introduce argon and oxygen mixed plasma, wherein the total flow rate of argon and oxygen is 100sccm; control the power to 600W, the gas pressure to 15Torr, the processing time to 4min, and control the oxygen flow rate in the plasma to 2sccm to obtain a nano-diamond / graphene composite vertical sheet film.
[0044] The surface morphology of the film was observed by field emission scanning electron microscopy; the phase composition of the sample was detected by visible light Raman spectroscopy; the microstructure of the sample was analyzed by high-resolution transmission electron microscopy; and the electrochemical properties of the film were determined by an electrochemical workstation.
[0045] Figure 5 This is a field emission scanning electron microscope photo of a NCD-VG2 sample with an oxygen content of 2 sccm at 50,000 times. It can be seen that the particle size does not change much, the lamellar structure between the particles disappears, the vertical lamellar layers on the surface begin to thin, and the film thickness is about 1.52μm.
[0046] Figure 6 This is the visible light Raman spectrum of the NCD-VG2 sample with an oxygen content of 2 sccm. The 1350, 1580, 1620, and 2700 cm -1 Four characteristic peaks, 1350cm -1 For sp 2 Disordered or defective D peak associated with bonded carbon, 1580 cm-1 For sp 2 G peak of bonded carbon, 1620 cm -1 D' peak related to graphite edge defects, also the characteristic peak of vertical graphene, 2700cm -1 It is a 2D peak with double frequency Raman characteristics due to the complete dispersion of phonons associated with single-layer or few-layer graphene. D / I G The value is 0.97, indicating that there are few defects inside the film. The half-peak width of the G peak is 37.02 cm -1 , indicating that the degree of disorder of graphite inside the film is low.
[0047] Figure 7 This is the HRTEM image of the NCD-VG2 sample with an oxygen content of 2 sccm. It can be seen from the image that the vertical layer structure of the particles has disappeared under the etching effect of the argon / oxygen mixed plasma. The SAED image shows the polycrystalline diffraction rings of diamond and the inner circle of graphite diffraction rings. The enlarged images of the two features of the vertical layer structure of this sample are shown in Figure 7 e and f in are given by Figure 7 As can be seen from the figure e, the vertical sheets in this area are composed of nanoparticle cluster structures. The corresponding FFT shows that the interior is a 0.209nm diamond (111) lattice, while the exterior of the particle shows 0.34nm interlaced graphite stripes, and the stripes are shorter, indicating that the etching effect of the plasma is enhanced, the graphite becomes shorter and the number of layers decreases. Figure 7 As can be seen in f, it is a long multi-layered strip structure, and its enlarged image shows a 0.34nm graphite lattice, indicating that it is a large-scale lamellar graphite structure remaining after treatment. At this time, the graphite phase components in the film have been significantly etched under the action of plasma, and the remaining are mainly large-scale thick graphite and short few-layer graphite structures around diamond grains.
[0048] Figure 8 The CV curves of NCD-VG2 samples with an oxygen content of 2 sccm at different scan rates are shown in Figure 2. It can be seen that the shape is close to a rectangle, indicating that it has certain double-layer capacitance characteristics. As the scan rate increases, the area of the CV curve also increases, which is caused by the increase in the diffusion resistance of electrolyte ions on the film surface. The calculated surface capacitance at a scanning voltage of 0.1 V / s is 1323.87 μF / cm 2 , showing higher capacitance.
[0049] Example 3
[0050] Diamond powder (Zhecheng Huifeng Diamond Technology Co., Ltd., particle size 500nm) and glycerol (glycerol) were mixed in a ratio of 1g:100ml, and ultrasonically dispersed for 20min to obtain diamond grinding paste; the diamond grinding paste was taken on a polishing flannel cloth and pressed on an intrinsic single crystal silicon wafer (Zhejiang Lijing Optoelectronics Technology, single-sided polished silicon wafer, thickness 500±10μm, diameter 100±0.4mm, resistivity 0.011-0.01Ωcm, model / crystal orientation: P <100> ) was polished back and forth at the grinding paste for 30 minutes, and the processed silicon wafer was ultrasonically cleaned in acetone and anhydrous ethanol for 5 minutes in turn, and dried with nitrogen to obtain single crystal silicon after seeding; the single crystal silicon after seeding was placed in a hot wire chemical vapor deposition device as a substrate, and acetone was used as a carbon source. The acetone was introduced into the reaction chamber by bubbling hydrogen with a flow rate of 90sccm, and pure hydrogen with a flow rate of 200sccm was also introduced. The growth power was controlled to 2200W and the growth pressure was 1.6kPa to grow a nano diamond particle layer for 20 minutes; the pure hydrogen flow rate was adjusted to 0sccm, the acetone flow rate was 100sccm, and the power was reduced to 1800W, grow vertical nano-diamond / graphene composite sheets for 3 minutes; stop introducing acetone, and slowly reduce the power to 0 at a rate of 0.5V / min to obtain a silicon wafer containing vertical nano-diamond / graphene composite sheets; place the silicon wafer with vertical nano-diamond / graphene composite sheets in a microwave plasma vapor deposition device, and introduce argon and oxygen mixed plasma, wherein the total flow rate of argon and oxygen is 100sccm; control the power to 600W, the gas pressure to 15Torr, the processing time to 4min, and control the oxygen flow rate in the plasma to 5sccm to obtain a nano-diamond / graphene composite vertical sheet film.
[0051] The surface morphology of the film was observed by field emission scanning electron microscopy; the phase composition of the sample was detected by visible light Raman spectroscopy; the microstructure of the sample was analyzed by high-resolution transmission electron microscopy; and the electrochemical properties of the film were determined by an electrochemical workstation.
[0052] Fig. 9 This is a field emission scanning electron microscope photo of the NCD-VG5 sample with an oxygen content of 5 sccm in the plasma at 50,000 times. It can be seen that the particle size is about 2μm, there is a certain gap between the particle layers, and the distribution on the surface has an obvious vertical layer structure. The thickness of the layers around is thinner than that in the middle, and the thickness is about 1.51μm.
[0053] Fig.10 The Raman spectrum of the NCD-VG5 sample with an oxygen content of 5 sccm. The 1350, 1580, 1620, and 2700 cm -1 Four characteristic peaks, 1350cm -1 For sp 2Disordered or defective D peak associated with bonded carbon, 1580 cm -1 For sp 2 G peak of bonded carbon, 1620 cm -1 D' peak related to graphite edge defects, also the characteristic peak of vertical graphene, 2700cm -1 It is a 2D peak of the double frequency Raman characteristic of the complete dispersion of phonons related to single-layer or few-layer graphene. With the increase of oxygen content, I D / I G The value of is reduced to 0.64, indicating that the internal defects of the film are reduced, and the half-peak width of the G peak is reduced to 29.97 cm -1 , indicating that the disorder degree of graphite inside the film continues to decrease.
[0054] Fig.11 This is the HRTEM image of the NCD-VG5 sample with an oxygen content of 5 sccm. It can be seen from the figure that there is a clear vertical layer structure outside the particle. The vertical layer structure of this sample shows two characteristics. The enlarged image is shown in Fig.11 b and c. Fig.11 As can be seen in b, the vertical lamellae in this area are composed of needle-like and nanoparticle cluster structures. The enlarged image of the nanoparticle cluster area and the FFT of the single grain area show that the interior is a 0.25nm diamond lattice, while the outside of the particle shows a 0.34nm graphite (002) lattice, but the number of layers is small (3 to 5 layers), indicating that the plasma etching effect on graphite is enhanced after the introduction of oxygen, the number of graphite layers is reduced, and part of it is converted into an amorphous phase structure. Compared with the NCD-VG2 sample, the graphite phase content in the sample is slightly reduced, the needle-like graphite stripes become lighter, the amorphous phase component increases, and the diamond grains are slightly larger.
[0055] Fig.12 The CV curves of NCD-VG5 samples with an oxygen content of 5 sccm at different scan rates are shown in Figure 2. It can be seen that the shape is close to a rectangle, indicating that it has certain double-layer capacitance characteristics. As the scan rate increases, the area of the CV curve also increases, which is caused by the increase in the diffusion resistance of electrolyte ions on the film surface. The surface capacitance at a scan voltage of 0.1 V / s is calculated to be 1068.01 μF / cm 2 , showing higher capacitance.
[0056] Comparative Example 1
[0057] The experimental conditions were consistent with those in Example 1, with the only difference being that the flow rate of oxygen in the plasma gas was changed to 10 sccm, and the capacitance of the nanodiamond / graphene composite vertical layer film was 1452.48 μF / cm 2 .
[0058] Comparative Example 2
[0059] The experimental conditions were consistent with those in Example 2, with the only difference being that the flow rate of oxygen in the plasma gas was changed to 15 sccm, and the capacitance of the nanodiamond / graphene composite vertical layer film was 369.96 μF / cm 2 .
[0060] Comparative Example 3
[0061] The experimental conditions were consistent with those in Example 3, with the only difference being that the flow rate of oxygen in the plasma gas was changed to 20 sccm, and the capacitance of the nanodiamond / graphene composite vertical layer film was 138.32 μF / cm 2 .
Claims
1. A nano-diamond / graphene composite vertical layer thin film electrode, characterized in that The nano-diamond / graphene composite vertical sheet thin film electrode is prepared as follows: (1) Pretreatment of single crystal silicon substrate surface grinding and seeding: diamond powder and glycerol are fully dispersed and mixed to obtain diamond grinding paste; the diamond grinding paste is taken on a polishing flannel cloth, and an intrinsic single crystal silicon wafer is pressed back and forth on the grinding paste for 5 to 40 minutes. The polished silicon wafer is ultrasonically cleaned in acetone and anhydrous ethanol for 1 to 30 minutes, and dried with nitrogen to obtain single crystal silicon after seeding; (2) growing a thin film by hot wire chemical vapor deposition: placing the seeded single crystal silicon described in step (1) as a substrate into a hot wire chemical vapor deposition device, using acetone as a carbon source, and introducing the acetone into the reaction chamber by bubbling hydrogen at a flow rate of 70-110 sccm, while also introducing pure hydrogen at a flow rate of 100-300 sccm, controlling the growth power to 2000-2600 W, and the growth pressure to 1.0-2.5 kPa to grow a nano-diamond particle layer for 10-50 min; adjusting the pure hydrogen flow rate to 0-20 sccm, the hydrogen flow rate to 50-100 sccm, reducing the power to 1300-1800 W, and growing a vertical nano-diamond / graphene composite layer for 0.5-10 min; stopping the introduction of pure hydrogen and acetone, and slowly reducing the power to 0 at a rate of 0.1-5 V / min to obtain a silicon wafer containing a vertical nano-diamond / graphene composite layer; (3) Microwave argon / oxygen mixed plasma etching treatment: Place the silicon wafer containing the vertical nano-diamond / graphene composite sheet layer described in step (2) in a microwave plasma vapor deposition device, introduce argon plasma or a mixed plasma of argon and oxygen, control the power to 400-800W, the gas pressure to 10-20Torr, the processing time to 2-8min, and the total plasma flow rate to 80-120sccm to obtain the nano-diamond / graphene composite vertical sheet film electrode; when the mixed plasma of argon and oxygen is introduced, the oxygen flow rate is 0-5sccm.
2. The nano-diamond / graphene composite vertical sheet thin film electrode according to claim 1, characterized in that: The particle size of the diamond powder described in step (1) is 500 nm.
3. The nano-diamond / graphene composite vertical sheet thin film electrode according to claim 1, characterized in that: The intrinsic single crystal silicon wafer in step (1) is a single-sided polished silicon wafer from Zhejiang Lijing Optoelectronics Technology Co., Ltd., with a thickness of 500±10μm, a diameter of 100±0.4mm, a resistivity of 0.011-0.01Ωcm, and a model / crystal orientation: P <100> .
4. The nano-diamond / graphene composite vertical sheet thin film electrode according to claim 1, characterized in that: The volume of the glycerol in step (1) is 50-150 mL / g based on the mass of the diamond powder.
5. The nano-diamond / graphene composite vertical sheet thin film electrode according to claim 1, characterized in that: In step (2), the acetone is introduced into the reaction chamber by bubbling hydrogen at a flow rate of 90 sccm, and pure hydrogen at a flow rate of 200 sccm is also introduced.
6. The nano-diamond / graphene composite vertical sheet thin film electrode according to claim 1, characterized in that: In step (2), the growth power is 2200 W, the growth pressure is 1.6 kPa, and the growth time is 20 min.
7. The nano-diamond / graphene composite vertical sheet thin film electrode according to claim 1, characterized in that: The total flow rate of the plasma in step (3) is 100 sccm.
8. The nano-diamond / graphene composite vertical sheet thin film electrode according to claim 1, characterized in that: In step (3), only argon plasma is introduced.
9. The nano-diamond / graphene composite vertical sheet thin film electrode according to claim 1, characterized in that: In step (3), the power is 600 W, the gas pressure is 15 Torr, and the processing time is 4 min.
10. The nano-diamond / graphene composite vertical sheet thin film electrode according to claim 1, characterized in that The nano-diamond / graphene composite vertical sheet thin film electrode is prepared as follows: (1) Pretreatment of single crystal silicon substrate surface grinding and seeding: diamond powder and glycerol are fully dispersed and mixed to obtain diamond grinding paste; the diamond grinding paste is taken on a polishing flannel cloth, and an intrinsic single crystal silicon wafer is pressed back and forth on the grinding paste for 30 minutes. The polished silicon wafer is ultrasonically cleaned in acetone and anhydrous ethanol for 5 minutes in turn, and dried with nitrogen to obtain single crystal silicon after seeding; The volume of the glycerol is 100 mL / g based on the mass of the diamond powder; (2) Hot wire chemical vapor deposition thin film growth: the single crystal silicon after seeding described in step (1) is placed as a substrate in a hot wire chemical vapor deposition device, acetone is used as a carbon source, and the acetone is introduced into the reaction chamber by bubbling hydrogen with a flow rate of 90 sccm. At the same time, a flow rate of 200 sccm is introduced, and the growth power is controlled to be 2200 W and the growth pressure is 1.6 kPa to grow a nano-diamond particle layer for 20 minutes; the pure hydrogen flow rate is adjusted to 0 sccm and the hydrogen flow rate is 100 sccm, and the power is reduced to 1800 W to grow a vertical nano-diamond / graphene composite layer for 3 minutes; the introduction of pure hydrogen and acetone is stopped, and the power is slowly reduced to 0 at 0.5 V / min to obtain a silicon wafer containing a vertical nano-diamond / graphene composite layer; (3) Microwave argon plasma etching treatment: Place the silicon wafer containing the vertical nanodiamond / graphene composite layer described in step (2) in a microwave plasma vapor deposition device, and introduce argon plasma, wherein the argon flow rate is 100 sccm; control the power to 600 W, the gas pressure to 15 Torr, and the processing time to 4 min to obtain the nanodiamond / graphene composite vertical layer thin film electrode.
Citation Information
Patent Citations
A kind of single particle layer nano-diamond film and preparation method thereof
CN104762607B
Nano diamond-graphene composite film electrode and preparation method thereof
CN111058011A
Diamond-graphene film with double-sided structure as well as preparation method thereof and application thereof
CN113881929A